Radiation Noise Reduction Using Vibrating Metamaterial Comprising a Spiral Absorber 나선형 흡진기로 구성된 진동 메타물질을 이용한 방사 소음 저감 - Ahn, Chang Hoon; Lee, Jin Woo (Transactions of the Korean Society of Mechanical Engineers, A, 2022)
In this paper, we propose a vibration metamaterial that effectively reduces radiated noise and demonstrate its performance in reducing radiated noise through experiments. Using a spiral beam-shaped absorber as a unit cell, local vibration is generated in the target frequency band. The dispersion curve calculated using the plane wave expansion method is compared with the finite element analysis result, and the relationship between the band gap and the radiated noise reduction band is identified. The effects of the dimensions, mass, and resonant frequency of the spiral absorber on the band gap are investigated. Based on these results, a unit cell for reducing radiation noise generated by the first natural mode of the beam is designed. The validity of the design result is verified through the vibro-acoustic reciprocity-based experiment for the vibration metamaterial. The results of this study can be applied to the suppression of radiated noise generated outside by panel vibration by mounting it inside the panel surrounding the mechanical product.
Keywords: Dispersion curves; Performance; Plane-waves expansion method; Radiated noise; Radiation noise; Spiral absorber; Spiral beams; Unit cells; Vibration metamaterial(; Vibro-acoustical reciprocity; Dispersion Curve; Plane Wave Expansion Method; Spiral Absorber; Vibration Metamaterial(; Vibro-Acoustical Reciprocity